PB-1-1 عرصه¬های کاربرد کلمه¬ی طیب در قرآن کریم و پیام¬های آن بر زندگی مسلمان - Ahmadi, Mohammad Sarwar (Farah Research and Scientific Journal, 2024)
The Holy Quran is a book whose combination of letters and the way its words are used in different sentences is a miracle and contains many benefits and wise tips; Accordingly, the word Tayyeb has been used many times in the Holy Quran, and I decided to organize a scientific research article under the title: "Areas of application of the word Tayyeb in the Holy Quran and its messages on Muslim life" The importance of research in this matter comes from the fact that this research is Quranic and is very valuable. Also, the concept of the word "Tayyeb" indicates goodness and purity, and naturally, in the areas where it is used, it includes the concepts of beauty. The word "Tayyeb" with its various combinations is mentioned 50 times in the Holy Quran and includes many fields. For example; bread and butter should be obtained in a clean way, wealth and capital should be used in a good and lawful way, the words of a Muslim should be good and he should present good children to the society. The important goal of this research is the lexical examination of the word Tayyeb and the expression of the fields in which it is used and the expression of social and educational messages and its effects on Muslim life. In this article, use the library and analytical method, and since this is a Qur'anic topic, the topic interpretation method is also used, firstly, the lexical aspect of the word Tayyeb is discussed, then the interpretation and analysis of the areas of use of the word Tayyeb are discussed.